Hidrólise protéica e remoção de fenilalanina, na obtenção de leite para pacientes fenilcetonúricos : emprego da protease do Aspergillus sojae e da subtilisina. - Mariana Wanessa Santana de Souza (2009)
Phenylketonuria (PKU) is a metabolic disease in which the untreated patients can show irreversible mental retardation, and the use of milk by phenylketonurics patients is forbidden . Aiming the development of milk with reduced Phe content to be used by phenylketonurics patients with no restriction, 32 conditions of enzymatic hydrolysis were tested employing, separately, a protease from Aspergillus sojae and a subtilisin, as well as some parameters of Phe removal were also evaluated, employing activated carbon (AC) as adsorbent support. The effects of reaction time and temperature, as well as of the enzyme:substrate ratio (E:S) and protein:activated carbon ratio were evaluated, aiming cost reduction and adjustment of the process for the scaling-up. After passing the milk containing hydrolyzed proteins through an AC column, the Phe content was evaluated by second derivative spectrophotometry (SDS). Thus, using the protease from A. sojae,the best result was obtained by using a reaction time of 3h, a temperature of 50 oC, an E:S ratio of 4:100 and a protein:AC ratio of 1:22, reaching 64.6% of Phe removal and a final content of 54.2mg/100 ml of milk. For subtilisin, the studied parameters that led to the highest Phe removal were almost the same as those observed for the A. sojae protease, except for the reaction time, which was 5h, obtaining 75.9% of removal which corresponds to a final Phe content of 36.9mg /100 ml. It can be inferred that both tested enzymes and the evaluated conditions showed to be efficient in obtaining milk with reduced Phe content, which is bellow the maximum limit stated by the Brazilian legislation.